Developing Mathematical Language Literacy Skills Through the Use of Indonesian in Learning Real Analysis Courses - Dewi Leni Mastuti; Buchari; Utin Desy Susiaty (Absis: Mathematics Education Journal, 2025)
The study's objectives are to: 1) ascertain the extent to which the teaching module aids in learning through the use of Indonesian in the Real Analysis course, and 2) ascertain the features of mathematical language literacy skills following participation in learning through the use of Indonesian in the Real Analysis course. This study used an experimental approach using Posttest-Only Control Design and True Experimental Designs research. Researchers administered an essay test consisting of up to four items to students in the real analysis lecture class in semester VI. The two-tailed significance level is 0.000, where <0.05. This indicates that there is a significant difference, at a probability of 0.05, between the outcomes of the mathematics language literacy skills learned using the Indonesian language actual analysis course teaching module. The mean difference column, which reads 15.31, indicates how much the average or mean of the two groups differed. It is possible to draw the conclusion that students who get instruction using the Indonesian language actual analysis course teaching module have superior mathematical language literacy skills compared to those who receive instruction using standard learning methods.